The Impact of Militarisation on Environmental Degradation in the E7 Countries: Panel CS-ARDL Approach - Akbulut Yildiz, Gizem; Yildiz, Barış; Al, İbrahim and Kanca, Osman Cenk (International Journal of Energy Economics and Policy, 2025)
This paper, within the framework of the Environmental Kuznets Curve (EKC), investigates the impact of militarisation on environmental degradation, including the role of renewable energy. Military expenditure and burden are used as proxies for militarisation, and models are estimated to quantify their relationship with carbon dioxide (CO2) emissions. The study utilizes the CS-ARDL approach to analyse data from Brazil, China, India, Indonesia, Mexico, Russia, and Turkey collectively known as the E7 nations from 1992 to 2022. The method employs both fixed-effect and random-effect models, taking into account short-run and long-run coefficients while accounting for cross-sectional dependencies and heterogeneities. The study puts forward four hypotheses for investigation, and a notable finding is that military expenditure, contradicting prevalent sustainability assumptions, has a substantial impact on the reduction of CO2 emissions over both short and long-run periods. This suggests that within the E7 context, militarisation may paradoxically function as a catalyst for environmental conservation rather than a detrimental impact. The findings further corroborate the inverted U-shaped EKC hypothesis by demonstrating that while economic growth initially increases emission levels, these levels begin to decline once a certain income threshold is reached. The study also underscores the long-run benefits of renewable energy in reducing CO2 emissions and advocates for investment in green energy projects, complemented by implementing viable environmental policies. These insights offer actionable guidance for policymakers seeking to harmonize economic development with environmental protection and sustainability objectives.